Pharyngeal airway space cephalometric evaluation in transverse maxillary deficient patients after SARME - Candido, Marcela Silva de Castro (2010)
Aim: To evaluate prospectively the upper airway of 16 patients submitted to surgically assisted rapid maxillary expansion. Methods: Volumetric tomography acquisitions were done preoperatively (T1) and after six months postoperatively (T2), the slices were obtained from the hard palate to the third cervical vertebra (C3), the images were imported and reconstructed in the Dolphin software for 2D definition of the upper airway. A cephalometric radiograph was generated by the software, the cephalometric points were traced at T1 and T2 for all patients in a dark environment always by the same operator and the Arnett-Gunson FAB Surgery analysis was applied. Results: A statistically significant reduction in area (p=0.03) at the level of the nasopharynx was observed, while at the oropharynx and hypopharynx it showed no statistical difference between T1 and T2. Conclusions: The area in the nasopharynx level presented a statistically significant decrease, however, despite the area decrease at this point, the patients seem to do better, and thus, this area decrease may not be clinically significant.